Outcomes after successful direct acting antiviral therapy for patients with chronic hepatitis C and decompensated cirrhosis - Cheung, Michelle C.M.; Walker, Alex J.; Hudson, Benjamin E.; Verma, Suman; McLauchlan, John; Mutimer, David J.; Brown, Ashley; Gelson, William T.H.; MacDonald, Douglas C.; Agarwal, Kosh; Foster, Graham R.; Irving, William L. (Elsevier, 2016)
Direct-acting antivirals have become widely used for patients with chronic hepatitis C virus infection with decompensated cirrhosis. Virological responses are excellent and early improvements in liver function, at least in a proportion of patients, have been observed but the longer term impact of viral clearance on end-stage liver disease complications is unclear. Background & Aims: Direct-acting antivirals have become widely used for patients with chronic hepatitis C virus infection with decompensated cirrhosis. Virological responses are excellent and early improvements in liver function, at least in a proportion of patients, have been observed but the longer term impact of viral clearance on end-stage liver disease complications is unclear. Methods: Prospective study of patients with decompensated cirrhosis who received 12 weeks of all-oral direct-acting antiviral through the English Expanded Access Programme. Endpoints were deaths, liver transplantation, hepatocellular carcinoma, serious decompensation events, sepsis or hospitalisations, and MELD scores between start of therapy to 15 months post-treatment start. An untreated cohort of patients was retrospectively studied over 6 months for comparison. Results: Amongst 317/406 patients who achieved sustained virological response at 24 weeks post-treatment, there were 9 deaths (3%), 17 new liver cancers (5%), 39 transplantations (12%) and 52 with serious decompensations (16%), over 15 months. When compared to the first six months from treatment start and to untreated patients, there was a reduction in incidence of decompensations [30/406 (7%) in months 6–15 and 72/406 (18%) in months 0–6 for treated patients vs. 73/261 (28%) in untreated patients]. There was no significant difference in liver cancer incidence (10/406 (2.5%) in months 6–15 and 17/406 (4%) in months 0-6 for treated patients vs. 11/261 (4%) in 43 untreated patients). Conclusions: This study suggests that antiviral therapy in patients with decompensated cirrhosis led to prolonged improvement in liver function, with no evidence of paradoxical adverse impact nor increase in liver malignancy. Lay summary: This is a report of a large group of patients in England who have hepatitis C virus (HCV) infection with advanced liver disease. They have been treated with new anti-HCV drugs, which cured the infection in the majority. This study looks at their outcomes a year following treatment, in terms of deaths, cancers and other complications of advanced liver disease. We conclude that in most patients anti-HCV treatment is beneficial even in advanced liver disease.